Batwoman. The complete first season [videorecording (DVD)] - Dries, Caroline (Warner Bros. Home Entertainment, 2020)
With Batman mysteriously AWOL, the police department has become weak and outgunned by criminal gangs. When the psychotic Alice and her Wonderland gang kidnap Sophie Moore, Kate Kane's ex-girlfriend, Kate has no choice but to put on a cape and cowl to continue the legacy of her missing cousin Bruce Wayne...as Batwoman. These 20 thrilling new episodes follow Gotham's newest symbol of hope as she struggles to overcome her own demons in order to save the city and the people she loves.